NICE guidelines on neonatal parenteral nutrition: a step towards standardised care but evidence is scarce - Webbe,J; Gale,C (The Lancet Child and Adolescent Health, 2020)
Globally, neonatal conditions are the leading cause of reductions in disability-adjusted life-years and affect outcomes that extend throughout life. Providing neonatal care to optimise such long-term outcomes is challenging because short-term research outcomes might conflict, even within individual trials. Evidence-based guidelines are a welcome tool to translate research into practice and reduce variation in care. Such standardisation of care can improve outcomes for patients. For example, adherence to a standardised guideline for enteral feeding is protective against necrotising enterocolitis, despite the heterogeneity in the content of the individual guidelines. The latest guideline by the UK's National Institute for Health and Care Excellence (NICE) on neonatal parenteral nutrition is a welcome addition to neonatal practice, and is particularly important given the deficiencies frequently found in the provision of neonatal nutritional care in the UK.